Escalation of tuberculosis notification: an analysis of associated social factors - Miandad, Muhammad; Nawaz-ul-Huda, Syed; Burke, Farkhunda; Azam, Muhammad; Khan, Imran (Bulletin of Geography. Socio-economic Series, 2016)
Studies have revealed that socioeconomic factors such as those pertaining to unmarried respondents, dependency, housing congestion and room sharing are associated with tuberculosis rates not only in developing countries but also in developed countries. Karachi has been identified as one of the most vulnerable cities where the spread of TB is increasing with the passage of time. The purpose of the present study is to assess TB notification with reference to some social factors in order that the findings of this study may provide helpful information for guidance related to social and economic policy formulation, at least at the local level to combat and eliminate tuberculosis. The methodology was based on NTP registered patients’ data and social factor analysis data which were acquired through questionnaire survey from notified patients. The result pertaining to TB notification reveals an increasing trend during the last seven years from 2007 until 2013. The notification of female patients compared to that of males is high, which is evidence of the fact that women in Pakistan are more affected but a comparison of patients to the total population in the respective years i.e. the patient population ratio, reveals a decreasing trend. The findings of the study emphasize that the problem of TB control can be resolved expeditiously with the cooperation of the public sector, which should be motivated to meet the core requirements of the programme at various administrative levels and strongly enforced standards of quality of lif